2006
DOI: 10.1007/s11269-006-2974-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Spatial Patterns of Drought on Different Time Scales: An Analysis of the Iberian Peninsula

Abstract: The differences in spatial patterns of drought over a range of time scales were analysed by the Standardized Precipitation Index (SPI). In a climatic area with a wide range of precipitation characteristics (the Iberian Peninsula), Pearson III distribution is flexible enough to calculate the drought index on different time scales. The Pearson III distribution was adapted to precipitation frequencies at time scales of 1, 3, 6, 12, 24 and 36 months. Spatial patterns of drought were analysed by Principal Component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
233
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 356 publications
(256 citation statements)
references
References 74 publications
(76 reference statements)
17
233
0
6
Order By: Relevance
“…An SPI of 0 indicates precipitation corresponding to 50% of the accumulated probability according to the Pearson III distribution. The complete formulation of the SPI calculation according to the Pearson III distribution and the L-moment method can be found in Vicente- Serrano and Cuadrat (2002) and Vicente-Serrano (2006).…”
Section: Drought Index Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…An SPI of 0 indicates precipitation corresponding to 50% of the accumulated probability according to the Pearson III distribution. The complete formulation of the SPI calculation according to the Pearson III distribution and the L-moment method can be found in Vicente- Serrano and Cuadrat (2002) and Vicente-Serrano (2006).…”
Section: Drought Index Calculationmentioning
confidence: 99%
“…To determine the general patterns of temporal evolution in the winter-SPI series, we used a PCA, which is widely used to analyse spatial and temporal patterns of droughts in different regions (Karl and Koscielny, 1982;Eder et al, 1987;Bonaccorso et al, 2003;Vicente-Serrano et al, 2004b;Vicente-Serrano, 2006). To summarise the general temporal patterns of droughts in the study area, we used a PCA in S-mode (Serrano et al, 1999), in which observatories are the variables and years the different cases.…”
Section: Analysis Of Drought Spatial and Temporal Patternsmentioning
confidence: 99%
“…These typically last for several months, or even years, and span thousands of square kilometres. Previous authors have considered the spatial and temporal nature of drought at regional (Livada and Assimakopoulos, 2007;Vicente-Serrano, 2006), continental (Briffa et al, 1994;Lloyd-Hughes and Saunders, 2002;van der Schrier et al, 2006) and global scales (Sheffield et al, 2009). A limitation of these studies is that they reduce the full 3-dimensional space-time drought structure to a lower order subspace.…”
Section: Introductionmentioning
confidence: 99%
“…McKee et al [18] suggested that the procedure of SPI can be applied to other variables relevant to drought, e.g., stream flow or groundwater. In addition to the gamma distribution, a range of other distributions (including those related to the gamma distribution) have been used to normalize [20,21], beta distributions and nonparametric approach kernel densities for soil moisture [22,23], log-normal for runoff [24], and six three-parameter distributions (lognormal, Pearson Type III, log-logistic, general extreme value, generalized Pareto, and Weibull) for streamflow [25].…”
Section: Standardized Precipitation Indexmentioning
confidence: 99%